Exploring the Experience of Employed Single Mothers in Raising Children - Dallakoti, Gita Naharki (NPRC Journal of Multidisciplinary Research, 2025)
Background: This qualitative study draws on in-depth, repeated narrative interviews with a single employed mother in urban Nepal. It explores her everyday struggles in balancing paid work and childcare within a patriarchal society where single mothers often face financial and time constraints, social stigma, and limited institutional support. The study specifically investigates how this mother manages time and resource constraints to meet her professional and personal commitments, and how she prioritizes her child’s needs over her own interests and desires. Methods: A qualitative narrative approach was used, and in-depth, repeated interviews were conducted with a single mother raising her daughter in difficult circumstances. The data were coded, categorized, and analyzed thematically using feminist and resilience theory frameworks to explore coping strategies, sacrifices, and resilience in the face of structural inequalities and societal discrimination. Findings: The results reveal that single mothers possess remarkable time management skills, often juggling multiple tasks and prioritizing their children's needs over their own comfort. Despite facing significant challenges, including limited resources, financial struggles, and a lack of social support, these mothers demonstrate exceptional resilience by putting their children’s futures first and taking on both maternal and paternal responsibilities. The study highlights how single mothers frequently sacrifice their own dreams, whether it is the prospect of remarrying or simply enjoying some downtime, to safeguard their children’s stability and emotional well-being. Furthermore, they work tirelessly to instil discipline, positive values, and a sense of social responsibility, striving to raise their children into strong and responsible individuals, despite the hurdles they encounter. Conclusion: In conclusion, the research highlights that working single mothers take on the dual roles of caregiver and provider, facing tremendous challenges with strength and commitment. Their sacrifices highlight the pressing need for supportive policies, inclusive social attitudes, and institutional support that recognize and uplift single mothers in the evolving family landscape of Nepal.